THE ROLE OF SOCIAL COMMUNICATION IN MUTUAL COOPERATION AND STABLE RELATIONS IN SOCIETY (World Bulletin of Social Sciences, 2025)
This article provides a philosophical analysis of the role and significance of social communication, which exists as an integral part of all relationships in social life, in the interconnectedness of the individual and society. The article highlights how such communication is observed in daily life, friendly and constructive relationships, and in political, economic, and social spheres, both among individuals and between social institutions. Moreover, it examines from a socio-philosophical perspective how mutually beneficial cooperation is ensured during the communication process and how it positively influences the establishment of stable social relations
Keywords: Communication; social communication; constructive communication